Interculturality in the Teaching of Philosophy Teachers: An Encounter with the Kcha'bli Community - Gómez Torres, Juan Rafael (2018)
This and the following writing were discussed at the meeting "Teaching Philosophy: Undisciplining Teaching," held from November 6 to 10, 2017 at the Department of Educology of the Center for Research and Teaching in Education (CIDE in Spanish), of Universidad Nacional, Costa Rica (UNA hereinafter). This event had the participation of Argentine panelists of great academic caliber, Dr. Alejandro Cerletti and Dr. Gabriela D'Odorico, both specialists and teacher trainers in the teaching of philosophy. As mentioned, this meeting had the particularity of being organized by students of the Philosophy Teaching major at UNA, specifically the students of the Pedagogical Module III: Research and Educational Innovation in the Teaching Practice of Philosophy Teaching (2017).